Fecal fat and energy loss in pancreas exocrine insufficiency: the role of pancreas enzyme replacement therapy. (2nd September 2018) - Erchinger, Friedemann; Øvre, Anne Kristine N.; Aarseth, Marita Malene; Engjom, Trond; Brønstad, Ingeborg; Dimcevski, Georg; Gudbrandsen, Oddrun Anita; Tjora, Erling
Abstract: Background: Chronic pancreatitis (CP) can lead to severe pancreatic exocrine insufficiency (PEI). Pancreatic enzyme replacement therapy (PERT) is well established, but knowledge of the physiological response to increasing doses on fecal fat- and energy loss is scarce. Methods: We included 10 patients with CP and established PEI and 12 healthy controls for a prospective interventional study. Subjects received no PERT in the first week followed by four weeks PERT incrementally increasing doses every week. For each week, three-day stool collection followed three days registration of nutritional intake. We measured the fecal output of fat and energy by van de Kamer titration and decomposition vessel calorimetry, respectively. We calculated fecal fat- and energy loss per day, the coefficient of fat absorption (CFA) and coefficient of energy absorption (CEA). Results: Without PERT treatment, CP patients with PEI had significantly higher daily fecal fat and energy loss ( p = .022; p = .035) compared to HC. In CP patients, there was a significant reduction of fecal fat and energy loss ( p = .045; p = .037) when PERT doses reached maximum intake of 75, 000 units per meal. In CP patients, there was a strong positive correlation between fecal loss of energy and fat ( r = 0.99), and between fecal loss of energy and daily stool weight ( r = 0.97). CFA and CEA correlated negatively with daily fecal fat loss ( r = −0.72) and fecal energy loss ( r = −0.65). Conclusions: PERT reduces fecal energy and fat loss in patients with CP and PEI. Fecal energy loss in CP patients is strongly dependent on fecal fat loss, and on fecal weight.